2014
DOI: 10.1186/1471-244x-14-106
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and prolonged grief in refugees exposed to trauma and loss

Abstract: BackgroundWhile a large proportion of conflict-affected populations have been dually exposed to trauma and loss, there is inadequate research identifying differential symptom profiles related to bereavement and trauma exposure in these groups. The objective of this study were to (1) determine whether there are distinct classes of posttraumatic stress disorder (PTSD) and prolonged grief disorder (PGD) symptoms in bereaved trauma survivors exposed to conflict and persecution, and (2) examine whether particular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
177
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(240 citation statements)
references
References 49 publications
30
177
6
2
Order By: Relevance
“…First, refugees are more likely to suffer from ongoing stressors that – combined with their complex psychiatric symptoms – can have a detrimental effect on their daily functioning and that can challenge treatment outcome (Craig, Sossou, Schnak, & Essex, 2008; Nickerson et al, 2014; Steel et al, 2011). Legal procedures, being separated from family and socioeconomic disadvantages, may all contribute to increased symptom severity and block symptom reduction (Schock, Böttche, Rosner, Wenk-Ansohn, & Knaevelsrud, 2016; Schock, Rosner, & Knaevelsrud, 2015; Steel et al, 2009, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, refugees are more likely to suffer from ongoing stressors that – combined with their complex psychiatric symptoms – can have a detrimental effect on their daily functioning and that can challenge treatment outcome (Craig, Sossou, Schnak, & Essex, 2008; Nickerson et al, 2014; Steel et al, 2011). Legal procedures, being separated from family and socioeconomic disadvantages, may all contribute to increased symptom severity and block symptom reduction (Schock, Böttche, Rosner, Wenk-Ansohn, & Knaevelsrud, 2016; Schock, Rosner, & Knaevelsrud, 2015; Steel et al, 2009, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation to new life events and stressors seems to challenge refugees. Nickerson et al (2014) found that after exposure to trauma and loss, different post-migration living difficulties are associated with specific symptom patterns regarding PCBD and PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has used latent class analysis (LCA) to identify groups of individuals based on the symptoms or symptom clusters of PGD, PTSD and/or depression, e.g. a resilient class, a predominately PGD or PTSD class and a combined PGD/PTSD or PGD/depression or PGD/PTSD/depression class (Boelen, Reijntjes, Aaam, & Smid, 2016; Boelen, Spuij, & Reijntjes, 2017; Djelantik, Smid, Kleber, & Boelen, 2017; Lenferink, De Keijser, Smid, Djelantik, & Boelen, 2017; Maccallum & Bryant, 2018; Nickerson et al, 2014). To our knowledge, only one research project has examined the latent groups among bereaved parents and reported that bereaved parents can be categorised into three different subgroups (i.e.…”
Section: Introductionmentioning
confidence: 99%